The Role and Status of National Research and Education Networks in Africa - Foley, Michael (The World Bank, 2016)
The aim of this report is to provide guidance to governments, institutions, and development partners on how to approach the provision of advanced information and communication technology (ICT) services to the higher education and research community in Africa. The timing is appropriate as it coincides with a transformation in the telecom infrastructure and services on the continent as fiber optic connectivity, both undersea and on land, is expanding at a rapid pace. The premise of the report that the organization of ICT services and connectivity is best provided by a dedicated organization called the National Research and Education Network (NREN) is based on international best practice and the current plans of the stakeholders in the region. In the following pages, the nature of NRENs and the case for their establishment is outlined and the story of their development in Africa up to their current status is described in operation of NRENs are discussed as a prelude to a guidance note on how to go about establishing or strengthening an NREN, with recommendations to the government, the private sector, institutions, and development partners